Enforcement of the income tax statement law to foreign companies taxable abroad in Indonesia - Maulana, Ayang Fristia; Khusaeni, Khusaeni; Choerunnisa, Najwa; Febriana, Hanum; Husna, Virda Sofiatul (Institute Of computer Science (IOCS), 2024)
This study discusses compliance with income tax (PPh) regulations for Indonesian tax collectors. In this study used library research and descriptive methods. Collecting taxes on the profits of foreign companies is one way the Indonesian government raises taxes. By increasing the number of foreign companies receiving funds from Indonesia through the General Administration to comply with the law as stipulated in the regulations of the Act No. 28 of 2007 on Taxation, as well as the Law No. 7 of 1983 on Income Tax. The tax authorities need to take further steps to ensure effective taxation of the profits of foreign companies in Indonesia. The aim of this effort is to ensure that receiving state taxes, especially taxes collected from foreign companies, is more effective.